After shrimp, tuna Is the second major export of Indonesian sead food <:ommodity group . Among the existing export mar1tets, Japan is the bigest mar1tet destination of Indonesian Tuna export. In the perspctive of Intemational trade, tuna· is a commodity group consisting of different kinds of export Item and specificity. Fresh ye//Owfin is the most Important Item of tuna group in term of export's value. This research specified model and estimated demand parameters of Japanese Impbrt marke - Suharno .; Heri Santoso (Buletin Ekonomi Perikanan, 2008)
After shrimp, tuna Is the second major export of Indonesian sead food <:ommodity group . Among the existing export mar1tets, Japan is the bigest mar1tet destination of Indonesian Tuna export. In the perspctive of Intemational trade, tuna· is a commodity group consisting of different kinds of export Item and specificity. Fresh ye//Owfin is the most Important Item of tuna group in term of export's value. This research specified model and estimated demand parameters of Japanese Impbrt market on Indonesia's fresh Ye//owfin. The estimation Is made In order to have valid Information especially for policy formulation. The estimation is done by using an econometric approach. In the approach three ad hoc models (linear, semi logarithmic and double logarithmic) were applied to a time series export data of Indonesian yellow fin to Japanese mar1tet by using ordinary least square (OLS) methods. These three models were then evaluated using three criteria of fitness: economic, statislical and econometric criteria. The model evaluation Indicated that semi-logarithmic model has the best fitness to the three criteria. COnsequently, the estimation of demand parameters is then made by using semi-logarithmic model. Using the semi-logarithmic demand model, the econometric analysis has indicated that Import of Indonesian Yellow fin by Japanese mar1tet is dependent on five factors: the domestic price of fresh yellow fin In Japan, Japanese GOP, Yen to dollar exchange rate, Intemational fresh shrimp price, and previous demand of fresh yellow fin by Japanese mar1tet. It is concluded that. of these five factors, two factors (own price and Income) revealed a Significant Interest. It Is found out that own price demand elasticity of fresh yellow fin Is elastic (-1,283) and demand elasticity of Income is inelastic (0,002) . The research recommended that Indonesian need to apply quality based strategy instead of price, by applying prudent production technology to anticipate the increasing Japanese GOP